Mdivi-1 Inhibits Astrocyte Activation and Astroglial Scar Formation and Enhances Axonal Regeneration after Spinal Cord Injury in Rats - Li, Gang; Cao, Yang; Shen, Feifei; Wang, Yangsong; Bai, Liangjie; Guo, Weidong; Bi, Yunlong; Lv, Gang; Fan, Zhongkai (Frontiers in Cellular Neuroscience, 2016)
After spinal cord injury (SCI), astrocytes become hypertrophic and proliferative, forming a dense network of astroglial processes at the site of the lesion. This constitutes a physical and biochemical barrier to axonal regeneration. Mitochondrial fission regulates cell cycle progression; inhibiting the cell cycle of astrocytes can reduce expression levels of axon growth-inhibitory molecules as well as astroglial scar formation after SCI. We therefore investigated how an inhibitor of mitochondrial fission, Mdivi-1, would affect astrocyte proliferation, astroglial scar formation, and axonal regeneration following SCI in rats. Western blot and immunofluorescent double-labeling showed that Mdivi-1 markedly reduced the expression of the astrocyte marker glial fibrillary acidic protein (GFAP), and a cell proliferation marker, proliferating cell nuclear antigen, in astrocytes 3 days after SCI. Moreover, Mdivi-1 decreased the expression of GFAP and neurocan, a chondroitin sulfate proteoglycan. Notably, immunofluorescent labeling and Nissl staining showed that Mdivi-1 elevated the production of growth-associated protein-43 and increased neuronal survival at 4 weeks after SCI. Finally, hematoxylin-eosin staining and behavioral evaluation of motor function indicated that Mdivi-1 also reduced cavity formation and improved motor function 4 weeks after SCI. Our results confirm that Mdivi-1 promotes motor function after SCI, and indicate that inhibiting mitochondrial fission using Mdivi-1 can inhibit astrocyte activation and astroglial scar formation and contribute to axonal regeneration after SCI in rats.